Dissection of intercellular communication using the transcriptome-based framework ICELLNET - Floriane Noël (Nature Portfolio, 2021)
Bulk and single-cell transcriptomic data can be a source of novel insights into how cells interact with each other. Here the authors develop ICELLNET, a global, biologically validated, and easy-to-use framework to dissect cell communication from individual or multiple cell-based transcriptomic profiles.